Implementasi Sistem Pendukung Keputusan Pemilihan Produk Terlaris Dengan Metode Simple Additive Weighting (SAW) Berbasis Web (Studi Kasus : Dapur Mama El) - Aditiya; Surtikanti (CV. Multi Kreasi Media, 2023)
To make it easier for potential customers to choose products, prospective customers cannot easily determine the choice of the best-selling products they want to choose. Prospective consumers consult with mama el kitchen business owners in determining the best-selling products. Mama El's kitchen business owners often find it difficult to help direct potential customers in making choices of existing products that match the criteria of these potential customers. Utilization of information technology is one way to make it easier for prospective customers to choose products to buy. Decision Support System (SPK) is a system that can help someone in making decisions from a problem. The purpose of this research is to build a best-selling product selection SPK study on mama el's kitchen using the Simple Additive Weighting (SAW) method. The SAW method can handle problems that have an element of uncertainty. The selection of best-selling products uses 4 criteria consisting of food price, food quality, food expiration time, and timeliness of manufacture. Then there are 5 alternatives with the data used according to the products sold by mama el's kitchen. This research produces SPK for selecting the best-selling products in mama el's kitchen and by using some sales data from the owner of mama el's kitchen to get the best-selling product results, on this research resulting in 5 rankings of the best-selling products with the first rank being ketapang seeds with calculation results 100,00, second nastar with calculation results 92,50, third kastengel with calculation results 75,36, fourth risoles with calculation results 52,86, and fifth rempeyek with calculation results 75,36. The system is expected to help prospective consumers in choosing the best-selling products that match the criteria of prospective consumers.